Bayesian stochastic dynamic models for internet auctions - Bradlow, Eric T. (Henry Stewart Talks, 2010)
Our integrated stochastic model approach, Data description, Empirical findings, Conceptual model development, Latent bidders, Model development, Model results, Model fit